The spectral appearance of primeval galaxies - Guiderdoni, B; Devriendt, J (1999)
The current and forthcoming observations of large samples of high-redshift galaxies selected according to various photometric and spectroscopic criteria can be interpreted in the context of galaxy formation, by means of models of evolving spectral energy distributions (SEDs). We hereafter present STARDUST which gives synthetic SEDs from the far UV to the submm wavelength range. These SEDs are designed to be implemented into semi-analytic models of galaxy formation.